1982
DOI: 10.1079/bjn19820013
|View full text |Cite
|
Sign up to set email alerts
|

Association of methanogenic bacteria with ovine rumen ciliates

Abstract: 1. The frequency of association between methanogenic bacteria and ovine rumen ciliates was studied in the rumen fluid of a fistulated sheep. 2.A period of fasting and flushing of the rumen content with nitrogen resulted in a relatively high association, whereas the intake of food and flushing with hydrogen caused a detachment of the methanogenic bacteria from the ciliates.3. The changes in the frequency of association can be correlated with the relative attribution to the H, production by hydrogenogenic bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(72 citation statements)
references
References 12 publications
(7 reference statements)
4
63
1
1
Order By: Relevance
“…H 2 is a fermentation by-product that is produced in large quantities by the protozoa in a specialised organelle equivalent to the mitochondria of aerobic eukaryotes: the hydrogenosome. This H 2 is utilised by methanogens that are found inside (Finlay et al, 1994) or in close association with protozoal cells (Stumm et al, 1982). This interaction is a typical example of interspecies H 2 transfer that favours both the methanogens and the protozoa (Hillman et al, 1988;Ushida et al, 1997).…”
Section: Protozoa and Methanogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 is a fermentation by-product that is produced in large quantities by the protozoa in a specialised organelle equivalent to the mitochondria of aerobic eukaryotes: the hydrogenosome. This H 2 is utilised by methanogens that are found inside (Finlay et al, 1994) or in close association with protozoal cells (Stumm et al, 1982). This interaction is a typical example of interspecies H 2 transfer that favours both the methanogens and the protozoa (Hillman et al, 1988;Ushida et al, 1997).…”
Section: Protozoa and Methanogenesismentioning
confidence: 99%
“…The extent of the association is influenced by diet and time of feeding (Stumm et al, 1982;Tokura et al, 1997). Adherence of methanogens to protozoa is low after feeding and appears to be related to the relative abundance of H 2 in the medium (Stumm et al, 1982). Most Entodiniomorphs seem able to carry methanogens on their surface, but no episymbiotic methanogens were observed associated with Holotrichs protozoa (Vogels et al, 1980).…”
Section: Protozoa and Methanogenesismentioning
confidence: 99%
“…Protozoa serve not only as host for methanogens, but also produce hydrogen in large quantities in a specialized organelle (hydrogenosome; Morgavi et al, 2010). This hydrogen is metabolized by methanogens that are found inside (Finlay et al, 1994) or in close association with protozoal cells (Stumm et al, 1982). The interaction between methanogens and protozoa is a typical example of interspecies hydrogen transfer, which favors both of them (Hillman et al, 1988;Ushida and Jouany, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Whitelaw et al (1984) observed that faunated cattle fed barley diets at restricted levels lost about 12% of GEI as CH 4 compared to 6-8% of GEI in ciliate-free animals. Protozoa in the rumen are associated with a high proportion of H 2 production, and are closely associated with methanogens by providing a habitat for up to 20% of rumen methanogens (Stumm et al 1982;Newbold et al 1995a). Finlay et al (1994) reported that protozoa could account for 37% of the total CH 4 production.…”
Section: Ionophoresmentioning
confidence: 99%